INDANG TIGO SANDIANG: TRANSPORMASI DARI SISTEM PENDIDIKAN SURAU KE DALAM BENTUK KEMASAN TARI POPULER DI KABUPATEN PADANG PARIAMAN SUMATERA BARAT - Surherni Surherni; Risnawati Risnawati; Syahril Anton (PROSIDING: SENI, TEKNOLOGI, DAN MASYARAKAT, 2019)
ABSTRACT The purpose of this study was to develop a performing art IndangTigoSandiangin a package of entertainment dance. Indang is a type of membranophone musical instrument - tambourine; the people of Pariaman called it rapa’i. Tigosandiang (three sides) refers to the formulation of performances come from three sects of Indang in Pariaman community - they call it guguih (cluster). The Guguih refers to: (1) GuguihKulipah (Khalifah) Husein; (2) GuguihKulipah (Khalifah) MakAmuik; and (3) GuguihKulipah (Khalifah) Tan Karim. The package was carried out through the concept of transformation with a touch of choreography and aesthetic values on the dance composition elements. The transformation of the dance development focuses on the elements of motion, including space, time, energy and music. In the element of space, the development covers the move-ment levels,the direction, focus of view, the volume and the pattern of movement. In the element of time, the development carried out is on the tempo and movement dynamics. While in the energy element, the develop-ment refers to the accentuation and quality of movement; the new nuance of music is cultivated in accordance to the artistic needs of dance development. This study uses two research methods, namely qualitative meth-ods and Research & Development (R & D). Qualitative methods in data collection are executed through observation, in-depth interviews, documentation; interpretative analysis is used to reveal the concept of IndangTigoSandiang in Pariaman community. Research & Deployment (R & D) based on qualitative research is carried out through the following stages: (1) product design; (2) design validation (3) design improvements; (4) product trials; (5) product revisions; (6) production. Through the emic approach, the results of this study indicate that IndangTigoSandiang has the potential to be developed to the package of entertainment dance in Pariaman community, West Sumatra.